2010
DOI: 10.1002/cem.1367
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate assessment of virtual screening experiments

Abstract: Discovering molecules with a desired biological function is one of the great challenges in drug research. To discover new lead molecules, virtual screens (VS) are often conducted, in which databases of molecules are screened for potential binders to a specific protein, using molecular docking. The choice of docking software and parameter settings within the software can significantly influence the outcome of a VS. In this study, we have applied chemometric methods such as design of experiments, principal compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…Five of the clusters contained lone compounds, all identified by our docking score resemblance approach. It has been shown that even quite similarly operating scoring functions favor different ligands as top candidates in virtual screening, , which would imply that considering several scoring functions could also increase the diversity among the top candidates, as seen in our results.…”
Section: Resultssupporting
confidence: 56%
“…Five of the clusters contained lone compounds, all identified by our docking score resemblance approach. It has been shown that even quite similarly operating scoring functions favor different ligands as top candidates in virtual screening, , which would imply that considering several scoring functions could also increase the diversity among the top candidates, as seen in our results.…”
Section: Resultssupporting
confidence: 56%
“…Most of the published structure-based virtual screens to identify new AChE inhibitors have been based on simulations in which enrichments of known inhibitors have been monitored [31] [37] . In general, these studies have found poor, or no enrichments of compounds binding to AChE [32] [36] , illustrating the challenges associated with docking of AChE inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The DUD set was chosen to best match ABL1 inhibitor-like ligands, and the Glide set is a universal decoy set. The DUD decoy set has been previously used for enrichment studies 28 . The DUD data set has been shown to include analog bias in the active ligand set.…”
Section: Discussionmentioning
confidence: 99%
“…Directory of Useful Decoys decoy set has been previously used for enrichment studies 28 . Using the Glide universal decoys, only 14.4% of decoys were predicted as hits.…”
Section: Discussionmentioning
confidence: 99%